Agroecological transitions: reading, writing, and thinking across disciplinary divides - Cusworth, George (Frontiers in Agronomy, 2024)
There is great diversity in the methods, terms, and empirical focuses employed by social and natural scientists working on agroecological transitions. The upshot is that whilst various researchers may nominally be putting their shoulder to the same agroecological wheel, the impact of their combined efforts is not what it might be. The aim of this article is to assist in the co-ordination and collaboration of disparate research activities and actors. It does so by offering the readers of this journal a user-friendly guide to some of the terms being used by social scientists (particularly human geographers and anthropologists) in their work on pests, diseases, crop protections and agroecological transitions. Such a document is of particular use as the terms and concepts employed by social scientists are equipped to generate analysis with explicit political insight in a way that those used by natural scientists may not be. The concepts and theories of social scientists foreground the commonalities that cut across case studies which might otherwise seem separated by a reservoir of context specificity. Tooled with these terms of analysis, the promise of agroecology rightly becomes something with far reaching political and justice consequences. These terms are presented across five areas: the ontological, the epistemological, the methodological, the historical, and the aesthetic. Given the range of social, ecological, cultural, and economic barriers involved in effecting an agroecological transition, it is vital that different researchers are conversant in each other's language.